A Pilot Nurse-Led Tele-Counseling Intervention to Parents of Children With Cerebral Visual Impairment on Adherence to Eye Activities During COVID-19 Pandemic: A Pre-experimental Study - Dhiman, Sonam; Saini, Sushma Kumari; Chaurasia, Shweta; Duggal, Mona; Miglani, Vaibhav; Raj, Srishti (Frontiers in Medicine, 2022)
Aim To assess the impact of a culturally appropriate and theoretically driven nurse-led tele-counseling intervention to parents of children with cerebral visual impairment (CVI) on the adherence to visual therapy advised by the ophthalmologists. Design A pre-experimental design was used. Methods Parents of children with CVI aged 2–9 years were enroled telephonically during the coronavirus disease 2019 (COVID-19) pandemic through the Pediatric Ophthalmology Clinic of a tertiary eye care center. Pre-assessment of participants was done telephonically as per the interview schedule. As per the protocol, the trained nurse-delivered tele-counseling intervention two times weekly for the first 2 weeks and weekly for the next 2 weeks via audio and video two-way tele-interaction with parents. A CVI information booklet was shared with parents via WhatsApp interface and individualized visual therapy was reinforced in accordance with the advice of the treating ophthalmologist. It was based on a thorough review of clinical records of the child, such as a detailed CVI questionnaire, history, and findings of clinical examination and neuro-visual behavior of a child. In addition, parents were encouraged to maintain a diary of the daily sessions of visual therapy and share recorded videos of their training exercises which were then evaluated and discussed with the ophthalmologist for any deviation. Outcome measures included adherence to eye activities for 7–8 sessions per day. Data were analyzed by using SPSS statistics for windows, version 20. Results Overall, improvement of adherence to visual therapy was observed among children with CVI (p < 0.0001). Nearly half (47.6%) of participants adhered to 3–4 sessions/day and only 28.6% were adherent to the recommended 7–8 sessions/day. Conclusion The pilot study demonstrated the potential of the nurse-led tele-counseling intervention to supplement the ongoing health treatment of patients in improving the adherence to eye activities among parents of children with CVI.